Advances in the bacterial organelles for CO2 fixation - Liu, Lu-Ning (Trends in microbiology (Regular ed.), 2022)
Carboxysomes are a family of bacterial microcompartments (BMCs), present in all cyanobacteria and some proteobacteria, which encapsulate the primary CO2-fixing enzyme, Rubisco, within a virus-like polyhedral protein shell. Carboxysomes provide significantly elevated levels of CO2 around Rubisco to maximize carboxylation and reduce wasteful photorespiration, thus functioning as the central CO2-fixation organelles of bacterial CO2-concentration mechanisms. Their intriguing architectural features allow carboxysomes to make a vast contribution to carbon assimilation on a global scale. In this review, we discuss recent research progress that provides new insights into the mechanisms of how carboxysomes are assembled and functionally maintained in bacteria and recent advances in synthetic biology to repurpose the metabolic module in diverse applications. CO2-concentrating mechanisms (CCMs) provide a means for accumulating CO2 around Rubisco to overcome the inherent limitations of Rubisco and enhance CO2 fixation.Carboxysomes are proteinaceous organelles in cyanobacteria and some proteobacteria which serve as the central CO2-fixing factory of CCMs.Carboxysomes sequester the cellular Rubisco and carbonic anhydrase from the cytoplasm, using a selectively permeable shell that structurally resembles virus capsids.Great efforts have been made recently to advance our understanding of the molecular mechanisms underlying carboxysome structure, assembly, biogenesis, and physiology.Advances in fundamental knowledge about carboxysome assembly and function has stimulated rational design and engineering of the protein organelles for improving CO2 fixation and new functions.